KOMPETENSI PEDAGOGIK GURU PPKn DALAM MENGAJAR PADA KELAS Vlll DI SMP NEGERI 6 SAMARINDA - Maulidini Risky Ariyanti; Aloysius Hardoko; M. Jamil; Asnar Asnar (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
Pedagogical competence represents the primary foundation for teachers in planning, implementing, and evaluating student-centered learning. This qualitative descriptive study aims to describe the pedagogical competence of Civic Education (PPKn) teachers in eighth-grade classes at SMP Negeri 6 Samarinda. Data were collected through observations across 4 learning sessions using the validated Teacher Performance Assessment Instrument (APKG), in-depth interviews with 1 main teacher and 6 students, and documentation reviews. APKG results yielded a mean score of 3.85 categorized as